Marketing Strategy of Bengkulu Local Coffee: SWOT, BCG, and Benchmarking (Case Study: Kopi 1001) - Suswati Nasution Rolies; Rina Trisnayanti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the strategy and position of the 1001 coffee brand and understand the market. The analysis used is SWOT analysis, BCG and Benchmarking. The results obtained, namely the results of the SWOT analysis, it is known that the main strategy for Kopi 1001 is the Growth strategy, where Kopi 1001 can increase sales with the advantages of its products and better use of promotions. BCG shows that Bengkulu City 1001 coffee is in a star position, which is in market share and high market growth. In this position, Kopi 1001 can implement a retrenchment strategy so that the business can survive in the face of competition from similar products. While the results of the benchmarking analysis show that 1001 coffee products have a distinctive robusta coffee taste and are safe for consumption, but product innovations need to be carried out that still maintain the characteristics of the coffee they have.